Frontiers of commercial real estate portfolio performance: Are sector-region-efficient diversification strategies a myth or reality?. Issue 2 (3rd April 2018) - Leone, Vitor; Ravishankar, Geetha
Abstract: This paper departs from the traditional optimisation methods used to evaluate portfolio performance. Rather, the Stochastic Frontier Analysis approach is used to econometrically determine the benchmark real estate portfolio frontier and subsequently assess the gains from diversifying real estate portfolios along regional and sectoral dimensions in the UK. Portfolio specific inefficiency measures are obtained which indicate whether a portfolio is efficiently diversified and therefore places on the benchmark frontier and if not, the degree to which performance can be improved is quantified. Portfolio-specific efficiencies average at 85–91%, indicating scope to further improve performance. Further, diversification be it on a sectoral or regional dimension, contributes to significantly lower variability in portfolio efficiencies.